3x^2-11x+6 x^3-2x^2-9x+18 2x^3-3x^2-2x+3

Question

3x^2-11x+6
x^3-2x^2-9x+18
2x^3-3x^2-2x+3

in progress 0
Serenity 5 tháng 2021-07-20T22:45:13+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-07-20T22:46:13+00:00

    Giải thích các bước giải:

     `3x^2-11x+6`

    `=(3x^2-9x)-(2x-6)`

    `=3x(x-3)-2(x-3)`

    `=(3x-2)(x-3)`

     `x^3-2x^2-9x+18`

    `=(x^3+3x^2)-(5x^2+15x)+(6x+18)`

    `=x^2(x+3)-5x(x+3)+6(x+3)`

    `=(x+3)(x^2-5x+6)`

    `=(x+3)[(x^2-2x)-(3x-6)]`

    `=(x+3)[(x(x-2)-3(x-2)]`

    `=(x+3)(x-2)(x-3)`

     `2x^3-3x^2-2x+3`

    `=(2x^3-3x^2)-(2x-3)`

    `=x^2(2x-3)-(2x-3)`

    `=(x^2-1)(2x-3)`

    `=(x-1)(x+1)(2x-3)`

    0
    2021-07-20T22:47:04+00:00

    Đáp án:

     

    Giải thích các bước giải:

    a) `3x^2-11x+6`

    `=(3x^2-9x)-(2x-6)`

    `=3x(x-3)-2(x-3)`

    `=(3x-2)(x-3)`

     b) `x^3-2x^2-9x+18`

    `=(x^3+3x^2)-(5x^2+15x)+(6x+18)`

    `=x^2(x+3)-5x(x+3)+6(x+3)`

    `=(x+3)(x^2-5x+6)`

    `=(x+3)[(x^2-2x)-(3x-6)]`

    `=(x+3)[(x(x-2)-3(x-2)]`

    `=(x+3)(x-2)(x-3)`

    c) `2x^3-3x^2-2x+3`

    `=(2x^3-3x^2)-(2x-3)`

    `=x^2(2x-3)-(2x-3)`

    `=(x^2-1)(2x-3)`

    `=(x-1)(x+1)(2x-3)`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )